RESULTS OF THE ANALYSIS OF INTRA- AND POSTOPERATIVE DATA IN PATIENTS OF REPRODUCTIVE AGE DURING LAPAROSCOPIC AND ROBOT-ASSISTED RADICAL INTERVENTIONS IN GYNECOLOGY - Glebov, Timur Alekseevich; Nizova, Daria Igorevna; Klyushnikov, Ivan Dmitrievich; Popov, Alexander Anatolyevich (Mother and Baby in Kuzbass, 2026)
Objective – to evaluate intra- and postoperative parameters in gynecological patients of reproductive age who underwent radical surgical treatment involving hysterectomy and tubal ablation using robotic and laparoscopic approaches, and to assess their quality of life 12 months after surgery.Material and methods. The retrospective study was conducted, including 80 patients who underwent radical surgery during reproductive age in the department of operative gynecology, gynecological oncology, and day hospital of the V.I. Krasnopolsky Moscow Regional Research Institute of Obstetrics and Gynecology (MONIOG) from 2018 to 2023. Intra- and postoperative parameters and quality of life were analyzed in these patients over the long-term period using questionnaires using the WHO Quality of Life Questionnaire (Abridged) (WHOQL-26) and the Female Sexual Function Index (FSFI).Results. The average age of the examined patients in the three groups was 40 ± 4.66 years. Intraoperative parameters did not differ significantly between robotic-assisted and laparoscopic extirpations. After surgical treatment using robotic and laparoscopic approaches, physical, psychological, and social problems were comparable, as were sexual function and satisfaction.Conclusion. Robotic technology can optimize the surgical approach with similar, if not better, results compared to the standard laparoscopic method. Women's quality of life is directly related to their overall physical, sexual, and psychological well-being. Radical surgical procedures for reproductive-aged patients directly impact these factors, which can lead to a decrease in quality of life.
Keywords: hysterectomy; robotic surgery; laparoscopy; quality of life; extirpation of the uterus